Human Mesenchymal Stem Cell Microvesicles for Treatment of Escherichia coli Endotoxin-Induced Acute Lung Injury in Mice. (3rd January 2014) - Zhu, Ying-gang; Feng, Xiao-mei; Abbott, Jason; Fang, Xiao-hui; Hao, Qi; Monsel, Antoine; Qu, Jie-ming; Matthay, Michael A.; Lee, Jae W.
Abstract: We previously found that human mesenchymal stem cells (MSC) or its conditioned medium restored lung protein permeability and reduced alveolar inflammation following Escherichia coli endotoxin-induced acute lung injury (ALI) in an ex vivo perfused human lung in part through the secretion of soluble factors such as keratinocyte growth factor (KGF). Recently, MSC were found to release microvesicles (MVs) that were biologically active because of the presence of mRNA or miRNA with reparative properties. MVs are circular fragments of membrane released from the endosomal compartment as exosomes or shed from the surface membranes. These studies were designed to determine if MVs released by human bone marrow derived MSCs would be effective in restoring lung protein permeability and reducing inflammation in E. coli endotoxin-induced ALI in C57BL/6 mice. The intratracheal instillation of MVs improved several indices of ALI at 48 hours. Compared to endotoxin-injured mice, MVs reduced extravascular lung water by 43% and reduced total protein levels in the bronchoalveolar lavage (BAL) fluid by 35%, demonstrating a reduction in pulmonary edema and lung protein permeability. MVs also reduced the influx of neutrophils and macrophage inflammatory protein-2 levels in the BAL fluid by 73% and 49%, respectively, demonstrating a reduction in inflammation. KGF siRNA-pretreatment of MSC partially eliminated the therapeutic effects of MVs released by MSCs, suggesting that KGF protein expression was important for the underlying mechanism. In summary, human MSC-derived MVs were therapeutically effective following E. coli endotoxin-induced ALI in mice in part through the expression of KGF mRNA in the injured alveolus. Stem Cells   2014;32:116–125